The Use of SPECT-CT to Define Treatment for Müller-Weiss Disease: A Prospective Radiographic and Clinical Study. Issue 4 (November 2022) - Sun, Chengyi; Ebben, Benjamin; Li, Shuyuan; Zhu, Mingjie; Myerson, Mark S.; Zhang, Ming-Zhu
Category: Hindfoot; Other Introduction/Purpose: Radiographic characteristics of Müller-Weiss disease (MWD) include compression and flattening of the lateral one-third of the tarsal navicular, lateral and inferior the shift of the talar head, followed by a varus hindfoot which produces a paradoxical planovarus. The radiographic Stage of the disease has no direct correlation with symptoms and therefore X-ray and CT have limitations in the surgical decision making for treatment. This study aimed to determine the predictive value of the use of SPECT-CT in surgical decision making. We hypothesized that SPECT-CT will highlight the specific joints actively involved in the disease process, and with the correct selective arthrodeses as well as intraoperative correction of malalignment of the hind and midfoot, improved clinical outcomes can be achieved. Methods: This was an IRB approved prospective study with 24 MWD patients (25 feet) enrolled. All patients failed conservative treatment and agreed to undergo SPECT-CT examination for further diagnostic purposes. The SPECT-CT scans were evaluated to identify the joints that were actively involved. Weightbearing X-rays (WBXR) and weightbearing CT scans (WBCT) were performed to assess the pre and postoperative midfoot and hindfoot alignment, including the talo-first metatarsal angle (TFMA), talonavicular coverage angle (TNCA), talocalcaneal angle (TCA), the Tomeno-Méary angle (TMA) and calcaneal pitch angle (CPA), and the hindfoot alignment angle (HAA). The surgical plan was based on the SPECT-CT and included guided arthrodesis, correction of hindfoot varus, talonavicular subluxation, and restoration of the medial arch. The AOFAS midfoot scale, visual analog scale (VAS), Foot and Ankle Ability Measure (FAAM) Sports subscale, and the 36-Item Short Form Health Survey (SF-36) were used pre and postoperatively to evaluate the clinical outcomes. Results: There were 20 females and 4 males with a mean age of 57.2 years and a mean duration of symptoms of 5.24 years. According to the Maceira staging system, there were 2 stage II, 8 stage III, 13 stage IV and 2 stage V. Three feet received isolated talonavicular arthrodesis, a talonavicular-cuneiform arthrodesis (10), triple arthrodesis (9), and triple plus navicular-cuneiform arthrodesis (3). The median follow-up time was 53.5 (range, 20-91) months. There were statistically significant improvements in the midfoot and hindfoot alignments (TNCA, TMA, CPA, HAA) and patient reported outcome measure scores (AOFAS, VAS, SF- 36 PF, SF-36 BP). Six patients required additional surgery (3 for hardware removal, and 3 for nonunion). No patient required revision surgery for arthritic pain in adjacent joints. Conclusion: SPECT-CT guided selective arthrodesis and correction of midfoot and hindfoot alignment can achieve both satisfactory clinical and radiographic outcomes in treating different stages of MWD. SPECT-CT is a very helpful tool to identify actively involved joints with arthritis secondary to the malalignment associated with this disease process, and avoids unnecessary arthrodesis of joints not actively involved in the disease process.